Menjembatani Generasi: Merancang Produk Asuransi Syariah yang Menjawab Kebutuhan Milenial dan Masa Depan - Dzikriansyah, Alief fikri; Kurniawati, Fitri (Diponegoro Journal of Islamic Economics and Business, 2023)
The development of sharia insurance in Indonesia is quite positive and has many enthusiasts because the majority of Indonesia's population is Muslim. Sharia insurance, also known as takaful or tadhamun, is an effort to protect each other and help each other among policy holders (participants) which is carried out through the collection and management of tabarru' funds which provide return patterns to face certain risks through appropriate contracts (engagements). with Islamic sharia. Millennials, defined as individuals born between 1981 and 1996, are a large generation and have significant influence on various sectors, including the insurance industry. The author uses this type of study in the form of a library survey (library research), namely research using data collection techniques through the study of literature, books, magazines and others that are considered according to this research. It can be concluded that by understanding the characteristics and needs of millennials, and utilizing technology and innovation, the sharia insurance industry can provide comprehensive financial solutions and in accordance with Islamic values for the millennial generation and the future.